Cold extraction of phenolic compounds from watercress by high hydrostatic pressure: Process modelling and optimization - Pinela, José (2018)
High hydrostatic pressure (HHP) was applied to the extraction of phenolic compounds from watercress (Nasturtium officinale). The process was optimized by response surface methodology using a five-level central composite design combining the independent variables of processing time (t, 1.5–33.5 min), pressure (P, 0.1–600 MPa) and solvent (S, 0–100% of ethanol, v/v). The individual and grouped phenolic compounds, analyzed by HPLC-DAD-ESI/MS, and the extraction yield were used as response variables. The theoretical models were fitted to the experimental data, statistically validated, and used in the prediction and optimization steps. The optimal HHP conditions for the extraction of phenolic compounds were: t = 3.1 min, P = 600 MPa and S = 100%, and originated 64.68 ± 2.97 mg/g of extract. This study highlighted the HHP as a promising technology to cold extract phenolic compounds (phenolic acids and flavonoids) from watercress in a selective way using a green solvent and reduced extraction times.